A Pre and post comparative study to assess the effectiveness of workshop conducted on research methods and scientific writing for first year medical students - Chakabarti, Sudakshina (International Journal of Psychosocial Rehabilitation, 2020)
For medical students, it is vital to keep in touch with the development information in the medical field. Hence it is better to encourage the medical students to share their findings or requirements through writing scientific articles in medical journals for wider reach. There are some barriers in writing scientific articles and it is essential to remove these barriers systematically. To understand the gaps in the knowledge about scientific writing of The objectives of the study were-To create awareness about scientific writing, reaserch methods through a 2 day workshop.To determine the awareness of MBBS students in writing and publishing scientific articles before and after a workshop through pre and post test analysis.A workshop on scientific writing and research methodology was conducted on 30 first MBBS students to create awareness and impart knowledge on scientific writing. A questionnaire was designed, validated, reviewed and tested to cover all aspects of writing an article and publishing it in a journal prior to the workshop so that it can be used as a pre and post testmaterial before and after the workshop. The survey study is conducted in the college environment as a 2 days program along with the workshop .Apart from encouraging the students to aim for writing various scientific articles, it also showsa way on how to refer various articles, select journals and improve acceptance of wri9tten articles for publication. The pretest and post test outcomes was tabulated and analysed. There is a significant improvement in knowledge of the participants on research method and scientific writing as the correct response in pretest was only 48% compared to the correct response in post test which increased to 70 %(Approx). The mean score of the knowledge level in pretest was 10.85 where as the mean score is 16.6. The attitude scale analysis showed the attitude of the participants towards the research and scientific writing too improved drastically in the post test. It is recommended to go for regular workshops to mitigate the gaps in the skill level of medical students starting from first year onwards. Continuous engagement of medical students in writing scientific articles would improve the communication between students, professors and medical professionals.